Burrowing pattern of lesser bandicoot rat (Bandicota bengalensis) in wheat (Triticum aestivum) crop in sandy-loam soil - SINGAL, RAJESH KUMAR; PASAHAN, S C (The Indian Journal of Agricultural Sciences, 2013)
Burrowing pattern of the lesser bandicoot rat [Bandicota bengalensis (Gray)] in wheat (TriticumÂ  aestivum L. emend. Fiori &. Paol.) crop in sandy-loam soil was studied in 1990-91. An increase in the total number of burrows of lesser bandicoot rat and their simultaneous transfer from the peripheral areas to inside the wheat crop field was observed with the advancement of crop growth. Most complicated burrows (average length 593.3 cm, breadth 325.0 cm and depth 52.7 cm) were excavated at tne maturity and post-harvest stages of wheat crop. B. bengalensis was found living in association with various other species like black ant (Monomorium indicum Ford.), lady-bird beetle (Cocctnella septumpunctata L.) and scorpion (Palamnaeus bengalensis Simon) in their burrows, preferring sandy-loam soil. Soil moisture had significant correlation with fluctuation in burrow density.